Redundant multiscale structure coding for error resilient video completion - Lei, Yang; Xiong, Hongkai (2008 IEEE International Symposium on Circuits and Systems, 2008)
The fundamental problem associating error resilience with vision-related technique is how to generate a plausible substitute for the unknown regions with complex and semantic structure, implicitly or explicitly by adding significant context redundancy to the coded video, subject to local similarity and global consistence in tempo-spatial domain. Following the structure-aware inpainting for image coding, an adaptive error resilience algorithm using redundant structure coding with multiscale B-spline based feature localization is proposed in this paper. In the proposed scheme, the curvature-based curve representation information extracted from original video pictures is coded and encapsulated into redundant slice of the H.264/AVC standard. To meet the required channel bandwidth and conditions, the underlying redundant structure coding allows for different representations with an optimal coding strategy from corresponding texture compressed version in the primary slice. With the proposed curvature and distortion measure, we can observe that acceptable compressed rate is achieved while progressive reconstruction accuracy is ensured.